COVID-19: IMPACTS ON INFORMATION ORGANIZATION, TRANSMISSION, AND USE [PRESENTATION] - Abruzzi, Raymond (Nazarbayev University Library, 2021)
The ways in which scholarly research outputs have been organized and disseminated have undergone some complete changes in the last decade, notably through the expansion of Open Access and the increased availability of such information outside of existing publishing channels. The crises related to COVID-19 and the demand for critical data and research findings needed to inform medical responses and public health and public policy decisions has increased the speed with which information has traveled along more traditional paths, but has also resulted in a substantial shift to new paradigms of information organization and sharing, as well as some improvement in international collaborations. This shift is not entirely new-- researchers tackling the challenges of earlier health crises (e.g., those engaged with mitigating the health impacts of the 1918 Influenza) had called for changes in the way information is organized and shared, as well as for greater collaboration amongst nations and institutions. The research communities grappling with COVID-19 have echoed those historical calls, and what has resulted is a rise (or, in some cases, an expansion) in the use of new methods for disseminating information including pre-print servers, rapid correspondence within peer-reviews publications, leveraging social media as a tool for disseminating data, and an increased demand for rapid digitization so that critical historical research might be more widely-available for use and analysis. This short talk will highlight examples of these new paradigms and discuss some of the long-term impacts that COVID-19 is likely having on the ways in which information is organized, transmitted, and used.
Keywords: Type of access: Open Access; EALC